Genome of the ramshorn snail Biomphalaria straminea—an obligate intermediate host of schistosomiasis. (15th February 2022) - Nong, Wenyan; Yu, Yifei; Aase-Remedios, Madeleine E; Xie, Yichun; So, Wai Lok; Li, Yiqian; Wong, Cheuk Fung; Baril, Toby; Law, Sean T S; Lai, Sheung Yee; Haimovitz, Jasmine; Swale, Thomas; et al.
Abstract: Background: Schistosomiasis, or bilharzia, is a parasitic disease caused by trematode flatworms of the genus Schistosoma . Infection by Schistosoma mansoni in humans results when cercariae emerge into water from freshwater snails in the genus Biomphalaria and seek out and penetrate human skin. The snail Biomphalaria straminea is native to South America and is now also present in Central America and China, and represents a potential vector host for spreading schistosomiasis. To date, genomic information for the genus is restricted to the neotropical species Biomphalaria glabrata . This limits understanding of the biology and management of other schistosomiasis vectors, such as B. straminea . Findings: Using a combination of Illumina short‐read, 10X Genomics linked‐read, and Hi‐C sequencing data, our 1.005 Gb B. straminea genome assembly is of high contiguity, with a scaffold N50 of 25.3 Mb. Transcriptomes from adults were also obtained. Developmental homeobox genes, hormonal genes, and stress-response genes were identified, and repeat content was annotated (40.68% of genomic content). Comparisons with other mollusc genomes (including Gastropoda, Bivalvia, and Cephalopoda) revealed syntenic conservation, patterns of homeobox gene linkage indicative of evolutionary changes to gene clusters, expansion of heat shock protein genes, and the presence of sesquiterpenoid and cholesterol metabolic pathway genes in Gastropoda. In addition, hormone treatment together with RT-qPCR assay reveal a sesquiterpenoid hormone responsive system in B. straminea, illustrating that this renowned insect hormonal system is also present in the lophotrochozoan lineage. Conclusion: This study provides the first genome assembly for the snail B. straminea and offers an unprecedented opportunity to address a variety of phenomena related to snail vectors of schistosomiasis, as well as evolutionary and genomics questions related to molluscs more widely.